Retention of mathematics and drug dosage calculation knowledge among undergraduate nursing students of a private school of nursing in Pakistan - Nishat Tabassum; Hussain Maqbool Ahmed Khuwaja (Journal of the Pakistan Medical Association, 2021)
This study aims to assess retention of drug dose calculation knowledge of undergraduate nursing students studying at a private school of nursing. This is a pre and post comparison design conducted at Aga Khan University, Pakistan from August, 2017 to September, 2019. All students enrolled in Bachelor of Science in Nursing (BScN) - Class of 2019 were enrolled. Mean test scores of 141 fourth year BScN students were compared with their own performance in second year. Mean scores on mathematics and drug dosage calculation test decreased significantly from 21 in 2nd year of studies to 17.97 in final year of studies. Modifications in assessments as well as curriculum are suggested to improve retention of dose calculation skills among undergraduate nursing students. Keywords: Nursing Education, Drug Calculation, Continuous...